Can Employee Competency Engage Islamic Banking Customers ? - Ria Mardiana Yusuf; Nurdjanah Hamid; Andi Ratna Sari Dewi; Hasnidar (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Islamic banking is demanded to continue improving in providing the best service to customers. It is not enough to understand how to keep customers doing transactions, companies must know that there are other ways consumers contribute to the company and stay engaged in itThe level of customer engagement can be shown in how involved they are with the company's offerings. The research team wanted to see how employee skills affected customer satisfaction. Makassar's Sharia Commercial Bank served as the study's sample institution. 200 questionnaires. The results of the study were processed using smartPLS 3. The results showed that employee competency has a significant effect on customer satisfaction, employee competency has no significant effect on customer engagement, and customer satisfaction has a significant effect on customer engagement.